The Oryza sativa stress associated protein (OsSAP) promoter modulates gene expression in response to abiotic stress by utilizing cis regulatory elements within the promoter region - Nur Aminah Mohd Hazbir; Khairun Nisha Japlus; Amirah Mohammad-Sidik; Su Datt Lam; Nurulhikma Md Isa (Penerbit Universiti Kebangsaan Malaysia, 2024)
The occurrence of extreme weather patterns induced by climate change has resulted in abiotic stress problems impacting the growth and productivity of plants. Rice (Oryza sativa), a staple food source for most Asians, is similarly affected by these challenges. Previous studies have identified the Oryza sativa Stress Associated Protein (OsSAP) genes to play a significant role in responding to abiotic stress. Among the 18 Stress Associated Protein members, OsSAP4 was highly expressed during drought and salinity conditions. Therefore, further experiments have been conducted, focusing specifically on the promoter region, to comprehend its regulation in response to abiotic stresses. Various types of cis-elements binding sites have been identified within the OsSAP4 promoter, encompassing MYB, CAMTA, CPP, C3H, HDZIP, bZIP, WRKY, and ERF. However, promoter analysis revealed that the distribution of the Cis-Regulatory elements bound by the Ethylene Response Factor (ERF) was the most prominent in the OsSAP4 promoter. Consequently, an analysis of promoter regulation was conducted using GUS reporter in Arabidopsis thaliana (A. thaliana) on two different sizes of OsSAP4 promoter sequences, each containing different quantities of ERF transcription factor binding sites. A noticeable difference in GUS staining activity was observed between pOsSAP4(1524 pb)::GUS and pOsSAP4(460 pb)::GUS, where pOsSAP4(1524 pb)::GUS exhibited higher GUS staining activity than pOsSAP4(460 pb)::GUS. The differences in GUS staining analysis are evident at the vegetative stage (leaf), silique, and inflorescence stages. This implies the participation of various other cis-element binding sites that influence the expression pattern of the OsSAP4 promoter during abiotic stress.